Thirty Years of Scholarly Influence in International Journals and Its Relation to the Most-Cited Scholars in Asian Criminology - Iratzoqui, Amaia (Asian journal of criminology, 2019)
Citation analysis provides a quantitative means of tracking the most influential scholars and works within a field. Despite this advantage, there is a dearth of research that provides more than a snapshot of influence over a relatively short time period. One exception is the citation analysis body of research conducted by Cohn and Farrington (1990, 2012), which has recently been expanded to include European (Cohn and Iratzoqui 2016) and Asian (Farrington et al. 2019) criminologies. The current paper presents a thirty-year analysis (1986-2015) of scholarly influence within four international journals (Australian and New Zealand Journal of Criminology, British Journal of Criminology, Canadian Journal of Criminology and Criminal Justice, and Criminology), as well as an analysis of the Asian Journal of Criminology (AJC) over its first 10-year period (2006-2015). The main conclusions are that, while rankings over time are not generally consistent within journals, the most-cited scholars tend to remain highly ranked over time across the four main international journals. Furthermore, the most highly cited scholars in the four international journals were also highly cited in AJC. The most-cited works of the top scholars across all of the international journals, including AJC, covered four major areas, including developmental and life-course criminology, theoretical issues, statistics, and policy issues.